FORMATION OF FULL COLLECTION OF SCELETONS FOR FREE CONCOURS - Alexander P. KOROBEINIKOV; Nikolay N. SADOVOY (Advanced Engineering Research)
Presentation algorithm of the closed contour in sceletons collection is presented. Sceletons collection represents sequence of segments which connect circle centers.  Circles fit into the generated contour segment. The major direction of algorithm usage is text information processing without setting up the certain type face.